Analisa Tebal Perkerasan Jalan Pada Proyek Pembangunan Jalan Banjar Sari Malakoni – Kayu Apuh (Pulau Enggano) - Wulan Puspa Anggraini (Jurnal Saintifik (Multi Science Journal), 2026)
This study aims to analyze the planning of strength and thickness of rigid pavement construction on the Banjar Sari Malakoni–Kayu Apuh Road in Enggano Island to ensure compliance with applicable technical standards and to support community traffic needs. The research method uses quantitative analysis based on the 2017 Pavement Design Manual, including flexural strength testing of concrete using the three-point loading method (ASTM C-78), subgrade CBR value analysis, and calculation of projected traffic growth over a 20-year design period. The results show that the road falls into the low traffic load category, with an effective CBR value of 19%, a concrete flexural strength of 3.3 MPa, and a JSKN value of 1.74 × 10⁶. The resulting pavement design applies a 4A type rigid pavement with a concrete slab thickness of 175 mm, a 125 mm aggregate base layer, and required crack distribution reinforcement without the use of dowels and LMC, indicating that the design is suitable to support the road’s technical and operational functions.